1988
DOI: 10.1002/1097-0142(19880415)61:8<1535::aid-cncr2820610809>3.0.co;2-e
|View full text |Cite
|
Sign up to set email alerts
|

Clinical diagnosis of late temporal lobe necrosis following radiation therapy for nasopharyngeal carcinoma

Abstract: The entire colonic mucosa of 51 cases of colorectal carcinoma was examined histologically. Mucosal lesions including goblet cell hyperplasia, crypt dilatation, ulceration with regeneration, basal cell hyperplasia, metaplastic lesions, and adenomas were encountered. Goblet cell hyperplasia (80.4%) was most prominent adjacent to the carcinoma (transitional mucosa). Whether this represents a precancerous change is controversial. Crypt dilatation (57%) is considered a nonspecific change due to mucosal injury and i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
113
2
1

Year Published

1995
1995
2017
2017

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 185 publications
(117 citation statements)
references
References 49 publications
1
113
2
1
Order By: Relevance
“…CT was found to be less sensitive, but those patients with positive CT manifested characteristic signs of nger-like hypodense areas and cyst-like shadows in the region of the temporal lobe. On the basis of histopathologic studies in these patients, Lee et al (20) suggested that the nger-like hypodense areas represented reactive white matter edema, while the cyst-like changes represented liquefactive necrosis with surrounding gliosis. In their study of a cohort of 60 patients treated for carcinoma of the nasopharynx, Leung et al (8) found a correlation between the volume of temporal lobe included in the high-dose region, the fractionation schemes employed, and the risk of temporal lobe injury.…”
Section: Imaging Studiesmentioning
confidence: 98%
See 4 more Smart Citations
“…CT was found to be less sensitive, but those patients with positive CT manifested characteristic signs of nger-like hypodense areas and cyst-like shadows in the region of the temporal lobe. On the basis of histopathologic studies in these patients, Lee et al (20) suggested that the nger-like hypodense areas represented reactive white matter edema, while the cyst-like changes represented liquefactive necrosis with surrounding gliosis. In their study of a cohort of 60 patients treated for carcinoma of the nasopharynx, Leung et al (8) found a correlation between the volume of temporal lobe included in the high-dose region, the fractionation schemes employed, and the risk of temporal lobe injury.…”
Section: Imaging Studiesmentioning
confidence: 98%
“…H owever, there are only a few reports on brain injury following irradiation for extracranial neoplasms of the head and neck (10,19,20). These patients typically present with memory impairment, headache, seizure or dysphasia and on further evaluation are found to have radiological changes compatible with brain injury.…”
Section: Clinical Ndingsmentioning
confidence: 99%
See 3 more Smart Citations